2010
DOI: 10.1038/sc.2010.88
|View full text |Cite
|
Sign up to set email alerts
|

Altered left ventricular diastolic function in subjects with spinal cord injury

Abstract: Study design: This is cross-sectional study. Objectives: The aim of this study is to investigate the cardiac structure and function of subjects with spinal cord injury (SCI) and the impact of metabolic, hemodynamic and inflammatory factors on these parameters. Setting: São Paulo, Brazil. Methods: Sixty-five nondiabetic, nonhypertensive, sedentary, nonsmoker men (34 with SCI and 31 healthy subjects) were evaluated by medical history, anthropometry, laboratory tests, analysis of hemodynamic and inflammatory para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 20 publications
1
22
0
6
Order By: Relevance
“…The diastolic function, as assessed by E, A and E/A ratio, was not significantly impaired in our SCI individuals. These data are consistent with those obtained by Eysmann et al 19 by conventional echocardiography, whereas more recently Matos-Sousa et al 4 demonstrated a lower early diastolic filling in a group of paraplegics compared with ABL subjects. Interestingly, we reported a higher IVRT in our SCI individuals, which may suggest some difficulties in the very early diastolic filling.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The diastolic function, as assessed by E, A and E/A ratio, was not significantly impaired in our SCI individuals. These data are consistent with those obtained by Eysmann et al 19 by conventional echocardiography, whereas more recently Matos-Sousa et al 4 demonstrated a lower early diastolic filling in a group of paraplegics compared with ABL subjects. Interestingly, we reported a higher IVRT in our SCI individuals, which may suggest some difficulties in the very early diastolic filling.…”
Section: Discussionsupporting
confidence: 82%
“…However, as recently proposed by Matos-Souza et al, 4 this may suggest that the chronically reduced venous return may have been compensated by a subsequent activation of the hormonal regulatory system, such as the renin-angiotensin-aldosterone system, in order to maintain blood pressure. This, in turn, may have stimulated LV remodeling, increasing LV wall thickness.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…We think chronic exposure to episodic hypertension because of AD may contribute to cardiac dysfunction after SCI because both clinical and preclinical studies reveal major similarities in the cardiac phenotype that develops in both hypertensive heart disease and SCI. [25][26][27][28][29][30][31][32][33] As such, the episodic hypertension commonly experienced in people with SCI during frequent bouts of AD may provide a potential explanation for the increased risk of heart disease in this population. Moreover, understanding how AD affects cardiac function in SCI may provide novel insight into the cardiac consequences of other conditions that are characterized by paroxysmal hypertension, such as preeclampsia or gestational hypertension, 34 as well as providing information on the relative hypertensive stimulus required for hypertensive heart disease.…”
Section: Hypertensionmentioning
confidence: 99%
“…
Subjects with chronic spinal cord injury (SCI) exhibit increased subclinical atherosclerosis and worse left ventricular diastolic function in comparison to able-bodied individuals, independent of traditional cardiovascular risk factors [1][2][3][4]. SCI may impair the descending spinal sympathetic tract and promote alterations in blood pressure (BP) profile, such as loss of nocturnal dipping due to orthostatic hypotension, and labile hypertension secondary to uncontrolled sympathetic output as a consequence of autonomic dysreflexia [5].
…”
mentioning
confidence: 99%